KEPEMIMPINAN PEREMPUAN PERSPEKTIF ISLAM DAN GENDER - Hikmatul Hasanah; Suprianik Suprianik (Institute for Research and Community Service, Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, East Java, Indonesia., 2019)
A woman has great potential, as well as a man, it can be seen from the various roles of woman needed in society, including: the role of reproduction, economic, social, political and Islamic leadership. However, in Islamic leadership, most women are only members of the management in social organizations, because they are deemed not have brave characteristics like men, except the social organization that all of the members are women. this is because women's interests are not accommodated in various political decisions. Education is the main factor that determines the activeness of women as administrators of political parties, obstacle experienced by women in political parties, including through a number of issues such as; education, employment, justice and gender equality, domestic roles, patriarchal culture, religion and family relationship. Woman, who has the competence to lead the country, could be heads of state in the modern society context, because the modern government system is not same with monarchy system in classical times, where the head of state must control all state affairs. Whereas in the modern era, there are separate sections in shaping the performance of leader of state. Seorang perempuan memiliki potensi yang besar, demikian pula halnya dengan laki-laki, hal ini terlihat dari berbagai peran yang dibutuhkan perempuan dalam masyarakat, antara lain: peran reproduksi, ekonomi, sosial, politik dan kepemimpinan Islam. Namun dalam kepemimpinan Islam, sebagian besar perempuan hanya menjadi pengurus dalam organisasi kemasyarakatan, karena dianggap tidak memiliki sifat pemberani seperti laki-laki, kecuali organisasi kemasyarakatan yang semua anggotanya adalah perempuan. Hal ini dikarenakan kepentingan perempuan tidak terakomodir dalam berbagai keputusan politik. Pendidikan merupakan faktor utama yang menentukan keaktifan perempuan sebagai pengurus partai politik, kendala yang dialami perempuan di partai politik, diantaranya melalui sejumlah isu seperti; pendidikan, pekerjaan, keadilan dan kesetaraan gender, peran rumah tangga, budaya patriarki, agama dan hubungan keluarga. Perempuan yang memiliki kompetensi memimpin negara dapat menjadi kepala negara dalam konteks masyarakat modern, karena sistem pemerintahan modern tidak sama dengan sistem monarki pada zaman klasik, dimana kepala negara harus menguasai semua urusan kenegaraan. Padahal di era modern, terdapat bagian tersendiri dalam membentuk kinerja pemimpin negara.